2002
DOI: 10.1046/j.1445-2197.2002.02509.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine: An aetiological contributor to peripheral vascular arterial disease

Abstract: Surgeons are increasingly being exposed to the term 'hyperhomocysteinaemia' but few understand this condition that affects up to 10% of the population, or its pathological sequelae. Hyperhomocysteinaemia has been identified as an important and independent risk factor for atherosclerosis. There is increasing evidence that, in addition to coronary disease, hyperhomocysteinaemia is also associated with an increased risk of developing peripheral arterial disease. Causes of elevated homocysteine levels include inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Hyperhomocysteinemia is a known independent risk factor for the development of PAD. 18 About 30% of patients with PAD have hyperhomocysteinemia, and their severity of disease is correlated with plasma homocysteine levels. 19 Folate supplementation has been shown to reduce plasma homocysteine levels in PAD patients, 20 and the addition of vitamins B 6 and B 12 may potentate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia is a known independent risk factor for the development of PAD. 18 About 30% of patients with PAD have hyperhomocysteinemia, and their severity of disease is correlated with plasma homocysteine levels. 19 Folate supplementation has been shown to reduce plasma homocysteine levels in PAD patients, 20 and the addition of vitamins B 6 and B 12 may potentate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Hcy levels increases the risk of developing peripheral vascular disease [38]. Hcy levels have been shown to be elevated in patients with peripheral vascular disease and chronic, non-healing lower-extremity ulcers [39-40].…”
Section: Pathophysiology Of Dpnmentioning
confidence: 99%
“…Homocysteine is a thiol‐containing amino acid that is formed when methionine is converted to cysteine 1 . Recent epidemiological and experimental studies have demonstrated that homocysteine acts as an independent risk factor for ischaemic heart disease, 2 cerebrovascular disease 3 and peripheral arterial disease 4 . Previous studies have shown that homocysteine accelerates the progression of cardiovascular diseases by inducing endothelial dysfunction and endothelial cell apoptosis, 5,6 oxidative stress, 7 proliferation of vascular smooth muscle cells 8 and platelet function injury 9 .…”
Section: Introductionmentioning
confidence: 99%